(3GdfcJ aj EYLGR GdbQBfs - (3CHh GdMSf GdQeGfj , Ydj Hf YjSi Hf Ydj Hf YHO Gddg, CHh GdMSf GdQeGfj,J (B384 (3g` s
(3ChdgG (B:s
(3bGd QMeg Gddg SCdJ habfG Gddg hEjGc Yf PcQ fcJ ai EYLGR GdbQBf Ohf GdJWhjd hLhg EYLGR GdbQBf JXgQ ef SHY LgGJ s
(3BNQgG (B:s
(3aGdYQH CbOQ Ydi GdHdGZI deG HjffG ef aWfJge deG dGjaWf dg GdehdO ef EbGeI GdEYQGH HGdWHGY aEPG YLRhG Yf Pdc aGdehdO Yfg CYLR ced hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1977s
Keywords: (3GdJaSjQ hYdhe GdbQBfs